Adapting façade performances to climate change in northern Europe: Analysis of future scenarios for an office building in Stockholm - Matteo Costanzo; Andrea Giovanni Mainini; Giuliana Iannaccone; Ivo Martinac; David Parsman (Acta Polytechnica CTU Proceedings)
Future climate change will affect many human activities and sectors. Among those, the built environment will face several challenges about the varying climate conditions, including increased demand for summer cooling and related heat stress indoor conditions. In this framework, the paper presents the results of a recent study that investigated the global warming impacts on energy demand and indoor climate comfort for an office building in Stockholm over the next 50-60 years. The future climate conditions were investigated in 2070 and 2080 with different climate morphing approaches. Three different passive cooling solutions to decrease the cooling demand (such as external roller shade, electrochromic glazing, and internally ventilated shading) have been preliminarily assessed about thermal and optical properties, then integrated into the building energy simulation software IDA-ICE to evaluate the building energy performances regarding different Swedish climates, and finally economically estimated with a simplified LCC analysis. The results indicated that an increment of the cooling demand from 3 up to 24 kWh/m2 and a reduction of the heating usage of 20-50 % will be experienced in 50-60 years. The different weather data morphing approaches displayed the inherent uncertainties when future evaluations are performed, although similar weather patterns were found. The improvement of the solar and optical properties indicated a lower cooling and ventilation usage with reductions of about 10-16 %. The electrochromic technology reported the lowest cooling demand (decrease up to 24 %), while the internally ventilated shading option outperformed the others with anannual energy consumption 4-9 % lower and the lowest LCC.